Left atrial size and strain in elite athletes: A cross‐sectional study at the NBA Draft Combine. Issue 7 (7th July 2020) - Cheema, Baljash; Kinno, Menhel; Gu, David; Ryan, Juliet; Mitter, Sumeet; Rigolin, Vera; Thomas, James; Puthumana, Jyothy
Abstract: Introduction: Atrial dilatation is common but of unclear physiologic significance in high‐performance athletes. Myocardial deformation analysis utilizing speckle‐tracking echocardiography has emerged as a promising tool to evaluate atrial function. In a cohort of elite basketball players attending the National Basketball Association (NBA) Draft Combine, we investigate changes in left atrial (LA) size as well as function as measured by strain. Methods and Results: From 2013 to 2018, all male athletes who attended the NBA Draft Combine in Chicago, IL, received a cardiac evaluation including a comprehensive transthoracic echocardiogram. Using the P‐wave as the reference point, speckle‐tracking was utilized to measure LA booster, conduit, and reservoir strain over one cardiac cycle. Left atrial volume index (LAVI) of ≥34 mL/m 2 was considered enlarged. 307 athletes received cardiac evaluation including a transthoracic echocardiogram, with 272 studies amenable for atrial strain analysis. Mean age was 21.0 years. Mean LAVI was 34.5 mL/m 2 and LAVI was enlarged in 131 (48.2%) athletes. Comparing LA strain in those with enlarged vs normal sized atria, reservoir strain was significantly reduced (32.1% [SD 6.0%] vs 35.2% [SD 8.2%], P  < .001), as was conduit strain (22.9% [SD 5.2%] vs 25.7% [SD 7.4%], P  < .001), with no difference seen in booster strain (9.2% [SD 2.1%] vs 9.4% [SD 2.7%], P  = .45). Conclusion: In this group of elite basketball players, LA enlargement was common and associated with reduced LA reservoir and conduit strain, with no difference in LA booster strain.